The relation between dust amount and galaxy mass across the cosmic time. Issue Volume 15:Issue S359(2020) (March 2019) - Barbosa-Santos, J. H.; Lima Neto, G. B.
Abstract: Dust Obscured Galaxies (DOGs) are observed as far as the reionization epoch. Their cosmic density peaks together with the star formation rate. DOGs also rule the star formation in high stellar mass galaxies. In this work we used a chemodynamical model to evolve the amount of dust in galaxies. We ran forty models varying initial mass and both dust formation efficiency and dust production. We find that for high star formation rate systems the accretion dominates the dust evolution and it explains high- z DOGs. Low star formation rate systems are better suited to investigate dust production. Also, we find that a M Dust / M Gas versus M Dust /M* diagram is a good tracer of galaxy evolution.